The evolution and maintenance of virulence in Staphylococcus aureus: a role for host-to-host transmission? - Massey, R; Horsburgh, M; Lina, G; Höök, M; Recker, M (2006)
Despite progress in our understanding of infectious disease biology and prevention, the conditions that select for the establishment and maintenance of microbial virulence remain enigmatic. To address this aspect of pathogen biology, we focus on two members of the Staphylococcus genus - Staphylococcus aureus and Staphylococcus epidermidis - and consider why S. aureus has evolved to become more virulent than S. epidermidis. Several hypotheses to explain this phenomenon are discussed and a mathematical model is used to argue that a complex transmission pathway is the key factor in explaining the evolution and maintenance of virulence in S. aureus. In the case of S. epidermidis, where skin contact affords easier transmission between hosts, high levels of virulence do not offer an advantage to this pathogen.